Ineffectiveness of pioglitazone in cognitive impairment induced by cyclophosphamide, methotrexate, and fluorouracil via oxidative stress and neuroinflammation - Alhowail, Ahmad Hamad (Frontiers in Neuroscience, 2025)
Research objectiveChemotherapy is frequently linked to enduring cognitive impairments in individuals who have survived cancer. The cyclophosphamide, methotrexate, and fluorouracil (CMF) regimen is a standard protocol in cancer treatment. Pioglitazone (PGZ), an oral medication used to treat diabetes, has demonstrated neuroprotective effects against certain chemotherapeutic agents, such as doxorubicin. This study aimed to evaluate the efficacy of PGZ in mitigating cognitive dysfunction caused by CMF.Materials and methodsForty male rats were allocated into four distinct groups: control, CMF-treated, PGZ-treated, and CMF + PGZ-treated, to evaluate survival rates, body weights, and cognitive performance using the Y-maze, novel object recognition test (NORT), and fear conditioning memory assessments. Furthermore, the investigation included an analysis of mitochondrial complex I activity, reactive oxygen species (ROS), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) within the hippocampus.ResultsThe CMF and CMF + PGZ groups exhibited decreased survival rates (50 and 40%, respectively) and reductions in body weight (16 and 11%, respectively). The Y-maze showed fewer entries and less time in the novel arm, but total entries were unchanged. The NORT revealed less exploration of the novel object in both CMF and CMF + PGZ groups. In fear conditioning, both groups showed reduced freezing time versus control, indicating memory impairment. Furthermore, mitochondrial complex I activity was diminished, and levels of ROS, TNF-α, and IL-1β were elevated in CMF; however, co-treatment with PGZ did not ameliorate these alterations.ConclusionThe CMF treatment resulted in cognitive dysfunction, and the addition of PGZ did not alleviate this neurotoxicity.